Comprehensive Analysis of Pedestrian Facilities in Citywalk Tegal City Using Global Walkability Index: A Comparative Assessment and Correlation Study - Agung Budi Dharmawan; Riska Dwi Anjani; Suprapto Hadi; Hanendyo Putro; Ahmad Basuki (Journal of Innovative and Creativity, 2025)
Pedestrian facilities serve as critical infrastructure in promoting sustainable urban mobility and reducing carbon emissions in modern cities. However, pedestrian lanes in Ahmad Yani Street, Tegal City face significant challenges including misuse for non-pedestrian activities such as unauthorized parking and informal trading, which compromises their primary function and safety standards. The study purpose was to conduct a comprehensive evaluation of pedestrian facility quality using the Global Walkability Index (GWI) methodology, establish correlational relationships between infrastructure parameters, compare performance across different street segments, and provide evidence-based improvement recommendations for Ahmad Yani Citywalk Street pedestrian infrastructure in Tegal City. This research employed a mixed-method approach combining systematic field observation surveys and structured questionnaires administered to 75 randomly selected respondents aged over 17 years. The evaluation utilized nine standardized GWI parameters assessed through a validated 1-5 Likert scale, with each parameter calibrated using established weighting coefficients. The research location encompassed Ahmad Yani Citywalk Street, spanning 700 meters and strategically divided into four analytical segments (Normal 1, Normal 2, Opposite 1, Opposite 2) to enable comprehensive comparative analysis. Statistical analysis included correlation coefficient calculations, variance analysis, and comparative performance assessments between segments. The comprehensive analysis revealed an average GWI score of 70.25, positioning the area within the "Supports walking activities" category. Significant variations were observed across parameters, with Parameter 1 (pedestrian lane availability) and Parameter 9 (street lighting) achieving the highest scores (3.75 and 3.00 respectively), while Parameter 8 (cleanliness and maintenance) recorded the lowest performance (2.25). Correlation analysis demonstrated strong positive relationships between safety parameters and user satisfaction (r=0.78, p<0.01), while environmental comfort showed moderate correlation with overall walkability perception (r=0.65, p<0.05). Comparative segment analysis revealed that Normal 1 achieved the highest individual performance (74), while Normal 2 demonstrated the most significant improvement potential with the lowest baseline score (66). Although pedestrian facilities demonstrate adequate basic infrastructure meeting minimum walkability standards, critical deficiencies require immediate attention including deteriorated zebra crossings, damaged disability accessibility features, inadequate cleanliness maintenance protocols, and insufficient enforcement of proper sidewalk utilization. The strong correlations identified between safety parameters and user satisfaction, combined with the significant performance variations across segments, indicate that targeted interventions focusing on high-impact, low-cost improvements could substantially enhance overall walkability performance and user experience.